2020
DOI: 10.1111/aji.13281
|View full text |Cite
|
Sign up to set email alerts
|

CD25+FOXP3+ and CD4+CD25+ cells distribution in decidual departments of women with severe and mild pre‐eclampsia: Comparison with healthy pregnancies

Abstract: ProblemThe aim of this study was to quantify and compare the distribution of regulatory CD25+FOXP3+ and activated CD4+CD25+ T cells in decidua basalis and parietalis of severe and mild pre‐eclampsia (PE) to normal healthy pregnancies.Method of studyDecidual tissue (decidua basalis and parietalis) of 13 women with mild PE, 15 women with severe PE, and 19 women with healthy term pregnancies were analyzed by immunohistochemistry and double immunofluorescence.ResultsThe total number of CD25+FOXP3+ cells/mm2 in dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…FOXP3 mRNA expression in CD8 + T cells was upregulated in our study, which was surprising as the results of numerous recent studies emphasize the role of regulatory CD4 + CD25 + FOXP3 + T cells for fetal acceptance [41][42][43][44][45][46]. The CD8 + FOXP3 + Treg subtype accounts for a small percentage of Treg cells and is much less studied compared to CD4 + FOXP3 + subpopulation.…”
Section: Discussioncontrasting
confidence: 80%
“…FOXP3 mRNA expression in CD8 + T cells was upregulated in our study, which was surprising as the results of numerous recent studies emphasize the role of regulatory CD4 + CD25 + FOXP3 + T cells for fetal acceptance [41][42][43][44][45][46]. The CD8 + FOXP3 + Treg subtype accounts for a small percentage of Treg cells and is much less studied compared to CD4 + FOXP3 + subpopulation.…”
Section: Discussioncontrasting
confidence: 80%
“…36,37 In humans, Treg cells are increased in the peripheral blood and decidua during pregnancy. 38,39 Though the alternation of decidual Treg cells in women with preeclampsia has been widely debated, [40][41][42][43][44][45][46] there is consensus on the functional or qualitative changes of Treg cells. 42,43,46 A report analyzing the T cell receptor repertoire of the effector Treg cells, which have particularly strong immunosuppressive activity, revealed that the decidual Treg cells had more clonally expanded TCR clonotypes than the peripheral blood in human pregnancies 46 ; this suggests that decidual Treg cells clonally increased in response to specific antigens in the fetomaternal interface.…”
Section: Maintenance Of An Allogeneic Pregnancy From Immunological As...mentioning
confidence: 99%
“…Tregs suppress other immune system cells through cell-cell interactions by receptors, including CTLA-4, PD-1, LAG-3, and Tim-3, and by the production of such cytokines as Il-10, IL-6, TGFβ, and Il-35 [2,3]. Dysfunction in Tregs has been extensively studied not only in cases of preterm birth and miscarriage [4,5], but also in cases of preeclampsia [6,7].…”
Section: Introductionmentioning
confidence: 99%